THE EFFECT OF MOTIVATION AND WORK ENVIRONMENT ON EMPLOYEE PRODUCTIVITY OF PT XYZ (Case Study in Assembly Plant C Department) - Novita Arianti; Budi Rismayadi; Neni Sumarni (Jurnal Ekonomi, 2023)
Every business unit wants high productivity because from that each business unit pays enough attention to the level of business productivity. Productivity is influenced by several factors, including motivation and work environment. This study aims to determine the direct influence between motivation and work environment on employee productivity and the indirect influence between motivation and work environment on employee productivity. This research was conducted at PT XYZ in Karawang Regency. The total sample taken was 150 respondents/employees from 240 existing populations. Data collection in this study was carried out through observation and questionnaires/questionnaires / written interviews. The data analysis technique carried out in this study was by path analysis of the application program using SPSS 26.0. Based on the results of the analysis found: 1). There is a correlation between the motivation variable (X1) and the work environment (X2) and has a fairly strong relationship. 2). The partial influence of the motivation variable (X1) on employee productivity (Y). 3). There is a partial influence of work environment variables (X2) on employee productivity (Y). 4). There is a significant simultaneous influence between motivation (X1) and work environment (X2) on employee productivity (Y).